Sintesis Bioplastik Self-Healing Berbasis Lignin Untuk Aplikasi Kemasan Ramah Lingkungan Data : Bibliometric Analysis di Laboratorium Teknik Industri Universitas Al-Azhar Medan - M Rizki Akbar Nasution; Galih Fachrezy (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2026)
The problem of environmental pollution caused by conventional plastic waste has driven the need for the development of sustainable alternative materials, one of which is lignin-based self-healing bioplastics for environmentally friendly packaging applications. However, research developments in this field remain scattered and have not been systematically mapped. This study aims to analyze scientific developments, research trends, and major thematic focuses related to the synthesis of lignin-based self-healing bioplastics using a bibliometric approach. Research data were obtained from the Scopus database with the criteria of Engineering subject area, article document type, English language, and publication period from 2021 to 2026, resulting in 3,294 scientific articles analyzed using VOSviewer software. The analysis results revealed three main research clusters: microbial-based biopolymer biosynthesis such as polyhydroxyalkanoate (PHA) and polyhydroxybutyrate (PHB), biomass utilization and biorefinery technology, and the development of lignin-based bioplastic composites with nanofillers to enhance mechanical properties and self-healing capability. The thematic map identified bioplastics and reinforced plastics as Motor Themes with high relevance and research maturity, while sustainable development and circular economy function as foundational themes. Overall, this study concludes that lignin has strong strategic potential as a core material in the development of self-healing bioplastics that support sustainability and the transition toward a green economy.